INOVASI PEMBELAJARAN BERBASIS PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA DI SD TUTUL 02 JEMBER - Faqih, Ahmad Muflih; M. Ilmi Zawawi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to examine the implementation of project-based learning (PjBL) in improving students' critical thinking skills at SD Tutul 02 Jember and understanding the dynamics of motivation and collaboration that accompany it. The phenomenon studied stems from the low analytical skills of students due to the dominance of rote-based learning in the context of rural elementary schools. The research uses a qualitative approach with a case study design, which allows in-depth exploration of the learning process in real situations. Data was collected through participant observation, semi-structured interviews with teachers and students, as well as documentation in the form of reflection journals, project results, and school archives. The research participants involved 10 fifth grade students with low critical thinking abilities and one science teacher as the learning implementer. The research results showed three main themes: (1) PjBL encourages students' cognitive involvement through contextual project activities based on the local environment; (2) learning motivation increases because students feel they have an active role in the learning process; and (3) group collaboration strengthens inference and evaluation skills through discussion and joint problem solving. These findings indicate that PjBL not only improves learning outcomes, but also changes learning interaction patterns from passive to participatory and reflective.